Understanding walkability criteria in high-density communities: a case study in Alexandria, Egypt - Maye Yehia; Yasmin Kandil; Noha A. Fouad (Renewable Energy and Sustainable Development, 2024)
Walkability has recently been a major topic and an essential attribute in the sustainability approach to urban design and planning. Studying urban dimensions and qualities in a specific context is essential to developing walkability criteria, as each environment has its conditions and spatial scale that will affect walkability scenarios differently. This paper studies the main criteria contributing to successful walkable environments in high-density communities. The methodology consists of developing detailed walkability criteria by studying urban qualities related to three dimensions: morphological/visual, functional, and social. Each urban quality is analyzed by stating its definition, assessment method and studying its condition in high-density communities. The assessment methods are based on quantitative and qualitative indicators depending on the nature of the criteria, which include imageability, transparency, scale of enclosure, complexity, connectivity, land use mix, legibility, as well as pedestrian comfort and safety. Providing tools to upgrade walkability in a city like Alexandria in Egypt is another objective of this study. Walkability criteria are tested on a typical city center street where buildings of every age and condition are mingled, and which is similar to many other Alexandria streets, thus, the results and recommendations can contribute to enhancing the walkability of everyday streets in the city.   Received: 21 January 2024 Accepted: 23 May 2024 Published: 30 June 2024